Entomological examination of the relationship between ante-mortem and post-mortem amitriptyline concentrations in insects - Sanyanga, Taremekedzwa (Division of Forensic Medicine and Toxicology, 2016)
When the death of an individual has occurred, the body of the deceased is not always discovered immediately and at times the body may be discovered after a long period of time. The consequence of discovering a body after a long period of time is that the body maybe found severely decomposed or skeletonized. As a result no viable blood, urine or tissue samples may exist that can be collected and utilized in toxicological analyses. Entomotoxicology offers a supplementary method to detect and analyse the presence of drugs post-mortem, especially in cases where viable toxicological specimens such as human tissue cannot be obtained. In South Africa and globally, standardised methodology is required to perform entomological examinations accurately, however due to the large variation of experimental set-up no such standardised methods yet exist. The main aim of the research was to analyse the effect of Amitriptyline on the development and growth rate of forensically important blow flies, and to investigate the potential in using blow fly larvae of the Western Cape, South Africa in forensic entomotoxicological analyses and future implementation. To achieve this blow fly species C. chloropyga and L. sericata were reared on homogenised pig liver containing 1000 mg/kg Amitriptyline until emergence of imago. The duration of time taken by the blow fly larvae species to reach 1 st , 2 nd , 3 rd , pupae and imago growth stages in the presence and absence of Amitriptyline was noted. The presence of drugs in larvae was investigated using high-pressure liquid chromatography coupled with dual mass spectrometry (HPLC/MS-MS). Amitriptyline was detected in all experimental larvae samples and was found to delay pupation by at least 26 hours and imago emergence by at least 72 hours. Amitriptyline however showed no distinct effect on C. chloropyga length and mass but was associated with a smaller length and mass in L. sericata compared to controls. Results indicate that entomotoxicology can be of use for qualitative analysis for the presence of Amitriptyline in forensic cases. Results also highlight the unpredictability of research using biological specimens.